CBMT-47. MODULATION OF NAD PATHWAYS AS A THERAPEUTIC STRATEGY FOR TARGETING IDH MUTANT GLIOMA. (11th November 2019) - Miller, Julie; Nagashima, Hiroaki; Fink, Alexandria; Tateishi, Kensuke; Wakimoto, Hiroaki; Banagis, Jack; Cahill, Daniel
Abstract: BACKGROUND: IDH mutant tumors exhibit an altered metabolic state which may be exploited for use as a novel therapeutic approach. Our previous work has shown the IDH mutant cancer survival is dependent on the biosynthetic enzyme, nicotinamide phosphoribosyltransferase (NAMPT), for the production of nicotinamide adenine (NAD). Inhibition of NAMPT activity (NAMPTi) efficiently targets IDH mutant cells. NAD steady-state is also influenced by consumptive processes that utilize NAD as a coenzyme, including Sirtuin (SIRT) signaling. To avoid concerns surrounding NAMPT inhibitor toxicity at high doses, we sought to investigate whether modulation of SIRT activity can effectively target IDH mutant cells. METHODS: IDH1 mutant cancer cells and patient-derived glioma lines were engineered for loss of SIRT gene expression using CRISPR/Cas9 gene editing or SIRT1 overexpression using a tetracycline-inducible expression system. The effect of silenced or enhanced SIRT1 activity was then assessed in IDH1 mutant cells alone or in combination with NAMPT inhibitors. RESULTS: Loss of SIRT1 expression, but not other SIRT family members, confers resistance to NAMPT inhibition in IDH1 mutant cells. Consistent with the hypothesis that SIRT1 is a major consumer of NAD, we observed a significantly smaller decline in NAD when SIRT1 is deleted. In agreement with these findings, when SIRT1 activity is enhanced from baseline by tetracycline-mediated induction of SIRT1 expression, IDH mutant cell growth is slowed. Further, overexpression of SIRT1 leads to decreased cell viability and enhanced NAD depletion when induced in combination with NAMPTi. CONCLUSIONS: IDH mutant tumors are vulnerable to NAD depletion. Our results show that this metabolic liability can be targeted by a combination of enhanced NAD consumption via SIRT1 activation and inhibition of NAD synthesis. Importantly, compounds to enhance SIRT1 activity are relatively non-toxic and in development for aging and neurologic disease, allowing potential for rapid translation to an IDH mutant-directed treatment.